Mutation breeding in small millets: approaches, advances, challenges, and prospects - Monika, S.; Chockalingam, Vanniarajan; Vetriventhan, Mani; Sakthivel K.; Ramesh, T.; Meena, Suresh (Springer, 2025)
Small millets are the tiny seeded members of the Poaceae family, which include crops such as finger millet, foxtail millet, barnyard millet, proso millet, kodo millet, little millet, teff, fonio, brown top millet, job’s tears, guinea millet, etc. Small millets play potentially significant roles in nutritional food security, climate resilience, and sustainability. Genetic improvement and scaling up of cultivation of improved varieties are expected to sustain millets production and productivity in the changing climate. Despite the availability of considerable small millets germplasm conserved in gene banks, their use has been limited due to many reasons including inadequate characterization, evaluation, data availability, and difficulty in hybridization resulting in limited opportunity for creating required variation through recombination breeding. Induced mutagenesis has been an alternate and important breeding approach used not only in the improvement of small millets through the creation of novel and useful variation but also nourishes the existing germplasm resources. Mutagenesis methods have evolved from creating random mutation to introduce site-specific gene modifications to become integral to any modern genetic and genomic study including gene/genome editing. Due to the challenges posed by regulatory policies, random conventional mutagenesis combined with next-generation sequencing could be still considered promising to detect genetic variations induced by mutation and in high throughput functional annotation of the mutated genes. Several mutation-based forward and reverse genetic techniques help in the development and characterization of novel mutant genotypic and phenotypic resources, which would accelerate the small millets improvement. This review furnishes the role of mutation in widening the genetic base by creating novel variations, its application in gene mapping, advancements in mutation using next-generation sequencing, different approaches, challenges, and prospects in small millets mutagenesis research.